An integrated microfluidic/microelectrode array for the study of activity-dependent intracellular dynamics in neuronal networks. Issue 22 (5th October 2018) - Moutaux, Eve; Charlot, Benoit; Genoux, Aurélie; Saudou, Frédéric; Cazorla, Maxime
Abstract : A microfluidics/MEA platform was developed to control neuronal activity while imaging intracellular dynamics within reconstituted neuronal networks. Abstract : In the central nervous system, neurons are organized in specific neural networks with distinct electrical patterns, input integration capacities, and intracellular dynamics. In order to better understand how neurons process information, it is crucial to keep the complex organization of brain circuits. However, performing subcellular investigations with high spatial and temporal resolution in vivo is technically challenging, especially in fine structures, such as axonal projections. Here, we present an on-a-chip system that combines a microfluidic platform with a dedicated matrix of electrodes to study activity-dependent dynamics in the physiological context of brain circuits. Because this system is compatible with high-resolution video-microscopy, it is possible to simultaneously record intracellular dynamics and electrical activity in presynaptic axonal projections and in their postsynaptic neuronal targets. Similarly, specific patterns of electrical activity can be applied to both compartments in order to investigate how intrinsic and network activities influence intracellular dynamics. The fluidic isolation of each compartment further allows the selective application of drugs at identified sites to study activity-dependent synaptic transmission. This integrated microfluidic/microelectrode array (microMEA) platform is a valuable tool for studying various intracellular and synaptic dynamics in response to neuronal activity in a physiologically relevant context that resembles in vivo brain circuits.